Priscilla Johnston

2022-01-06

movingsupplyw1

Beginner2022-01-07Added 30 answers

Solution:

$(4-x{y}^{2})dx+(x+{x}^{2}{y}^{2})dx=0$

$(4dx+xdy)-(x{y}^{2}dy-{x}^{2}{y}^{2})=0$

$d\left(xy\right)-{\left(xy\right)}^{2}[\frac{dx}{x}-dy]=0$

$\int \frac{d\left(xy\right)}{{\left(xy\right)}^{2}}-\int \frac{dx}{x}+\int dy=0$

$\Rightarrow -\frac{1}{x\cdot y}-\mathrm{ln}x+y=C$

put$4\left(1\right)=1$

$-\frac{1}{1\cdot 1}-\mathrm{ln}1+1=C\Rightarrow -1-0+1=C$

$c=0$

Hence,$-\frac{1}{x\cdot y}\cdot \mathrm{ln}x+y=0$

put

Hence,

SlabydouluS62

Skilled2022-01-08Added 52 answers

Consider the differential equation

$(y-x{y}^{2})dx+(x+{x}^{2}{y}^{2})dy=0$

$ydx-x{y}^{2}dx+xdy+{x}^{2}{y}^{2}dy=0$

$(ydx+xdy)+({x}^{2}{y}^{2}dy-x{y}^{2}dx)=0$

$d\left(xy\right)+xy(xydy-ydx)=0$

$d\left(xy\right)+{x}^{2}{y}^{2}dy-x{y}^{2}dx=0$

Dividing by$x}^{2}{y}^{2$

$d\frac{xy}{{x}^{2}{y}^{2}}+dy-\frac{dx}{x}=0$

$d\frac{xy}{{\left(xy\right)}^{2}}+dy-\frac{dx}{x}=0$

Integrating the equation above we get

$\int \left[d\frac{xy}{{\left(xy\right)}^{2}}\right]+\int dy-\int \frac{dx}{x}=C$ …..(1)

Where C is constant of integration

Now say$\int \frac{dz}{{z}^{2}}=-\frac{1}{z}$

$\int {x}^{n}dx={x}^{n}+\frac{1}{n+1}+c\text{}\text{for}\text{}n\ne -1$

$\int \frac{dx}{x}=\mathrm{ln}x+c$

Using these identities if$z=xy$ then the above eqn.(1) becomes

$-\frac{1}{xy}+y-\mathrm{ln}x=C$

Multiply throughout by xy in the above equation we get

$-1+x{y}^{2}-xy\mathrm{ln}x=Cxy$

Therefore the solution of the equation is

$x{y}^{2}-xy\mathrm{ln}x-1=Cxy$ .

Where C is any arbitrary constant.

Dividing by

Integrating the equation above we get

Where C is constant of integration

Now say

Using these identities if

Multiply throughout by xy in the above equation we get

Therefore the solution of the equation is

Where C is any arbitrary constant.

- A body falls from rest against resistance proportional to the square root of the speed at any instant. If the body attains speed V1 and V2 feet per second, after 1 and 2 seconds in motion, respectively, find an expression for the limiting velocity.

The Laplace transform of the product of two functions is the product of the Laplace transforms of each given function. True or False

The Laplace transform of

is$u(t-2)$

(a)$\frac{1}{s}+2$

(b)$\frac{1}{s}-2$

(c) ??$e}^{2}\frac{s}{s}\left(d\right)\frac{{e}^{-2s}}{s$ 1 degree on celsius scale is equal to

A) $\frac{9}{5}$ degree on fahrenheit scale

B) $\frac{5}{9}$ degree on fahrenheit scale

C) 1 degree on fahrenheit scale

D) 5 degree on fahrenheit scaleThe Laplace transform of $t{e}^{t}$ is A. $\frac{s}{(s+1{)}^{2}}$ B. $\frac{1}{(s-1{)}^{2}}$ C. $\frac{s}{(s+1{)}^{2}}$ D. $\frac{s}{(s-1)}$

What is the Laplace transform of

into the s domain?$t\mathrm{cos}t$ Find the general solution of the given differential equation:

${y}^{\u2033}-2{y}^{\prime}+y=0$The rate at which a body cools is proportional to the difference in

temperature between the body and its surroundings. If a body in air

at 0℃ will cool from 200℃ 𝑡𝑜 100℃ in 40 minutes, how many more

minutes will it take the body to cool from 100℃ 𝑡𝑜 50℃ ?A body falls from rest against a resistance proportional to the velocity at any instant. If the limiting velocity is 60fps and the body attains half that velocity in 1 second, find the initial velocity.

What's the correct way to go about computing the Inverse Laplace transform of this?

$\frac{-2s+1}{({s}^{2}+2s+5)}$

I Completed the square on the bottom but what do you do now?

$\frac{-2s+1}{(s+1{)}^{2}+4}$How to find inverse Laplace transform of the following function?

$X(s)=\frac{s}{{s}^{4}+1}$

I tried to use the definition: $f(t)={\mathcal{L}}^{-1}\{F(s)\}=\frac{1}{2\pi i}\underset{T\to \mathrm{\infty}}{lim}{\int}_{\gamma -iT}^{\gamma +iT}{e}^{st}F(s)\phantom{\rule{thinmathspace}{0ex}}ds$or the partial fraction expansion but I have not achieved results.How do i find the lapalace transorm of this intergral using the convolution theorem? ${\int}_{0}^{t}{e}^{-x}\mathrm{cos}x\phantom{\rule{thinmathspace}{0ex}}dx$

How can I solve this differential equation? : $xydx-({x}^{2}+1)dy=0$

Find the inverse Laplace transform of $\frac{{s}^{2}-4s-4}{{s}^{4}+8{s}^{2}+16}$

inverse laplace transform - with symbolic variables:

$F(s)=\frac{2{s}^{2}+(a-6b)s+{a}^{2}-4ab}{({s}^{2}-{a}^{2})(s-2b)}$

My steps:

$F(s)=\frac{2{s}^{2}+(a-6b)s+{a}^{2}-4ab}{(s+a)(s-a)(s-2b)}$

$=\frac{A}{s+a}+\frac{B}{s-a}+\frac{C}{s-2b}+K$

$K=0$

$A=F(s)\ast (s+a)$